The Impact of Income Diversification on Bank Stability in Indonesia: A Comparative Analysis of Conventional and Sharia Banks - Juwita Daria; Khaira Amalia Fachrudin; Syahyunan Syahyunan; Nisrul Irawati (Indatu Journal of Management and Accounting, 2025)
Banks play a major role in economic activities worldwide, but until now, there has been no clear consensus on the impact of income diversification on bank stability and its potential to help banks survive during a crisis, especially when relying on interest income. This study aims to determine whether income diversification affects the stability of Islamic and conventional banks in Indonesia during the period 2019–2023. This research uses quantitative data from 10 samples over five years, selected through the purposive sampling method. The study finds that income diversification has a significant positive effect on the stability of Islamic banks but is not significant for the stability of conventional banks. This indicates that income diversification can significantly enhance the stability of Islamic banks, while for conventional banks, it has the potential to improve stability. Overall, income diversification has different impacts on different types of banks. Bank debt has a negative but insignificant effect on the stability of both conventional and Islamic banks, showing a similar effect across bank types. Bank size has a positive but insignificant effect on conventional bank stability, while it has a positive and significant effect on Islamic bank stability, indicating differences in the impact of bank size on different types of banks. This study is a pioneering assessment of the effect of income diversification on the major types of banks in Indonesia (Islamic and conventional) and is expected to be useful for banking management, decision-makers with religious investment considerations, and regulators.